Buobellenden jingyuanensis gen. et sp. nov. of the subfamily Pselaphinae (Coleoptera, Staphylinidae) from Northwestern China - Yin, Zi-Wei; Nomura, Shûhei; Zhao, Mei-Jun (Zootaxa, 2009)
Buobellenden jingyuanensis gen. et sp. nov. (type locality Liupanshan National Nature Reserve, Ningxia Autonomous Region, China) is described and illustrated. Its systematic position is discussed. The new genus is characterized by the maxillary palpi with 4th segment broadened throughout length and the apex of each paramere with two long setae. The pselaphine tribe Pselaphini Latreille, 1802 is clearly separated from allied tribes by the single claw of the tarsus and large terminal segment of the maxillary palpus. Up to the present, 12 genera of Pselaphini were recorded from the Palaearctic region: Pselaphus Herbst, 1792; Curculionellus Westwood, 1870; Tyraphus Sharp, 1874; Dicentrius Reitter, 1882; Mentraphus Sharp, 1883; Pselaphostomus Reitter, 1909; Pselaphaulax Reitter, 1909; Pselaphogenius Reitter, 1910; Afropselaphus Jeannel, 1950; Geopselaphus Jeannel, 1956; Pselaphotrichus Besuchet, 1986; and Hirashimanymus Nomura, 1990. During June 2008, we visited the Liupanshan National Nature Reserve, Ningxia Autonomous Region of China and collected pselaphines from sifted samples using berlese funnels. This resulted in the discovery of specimens representing a new genus of Pselaphini, which is described and illustrated herein. Specimens were killed with ethyl acetate and dried. Dissections were made in 75% ethanol. Genitalia and small parts were mounted in Euparal (Chroma Geselschaft Schmidt, Koengen, Germany) on plastic slides. Drawings were made using an Olympus SZ40 stereoscope and an Olympus CX21 microscope. The photo was taken using an Olympus C-5050 camera mounted on an Olympus SZX12 stereoscope.